The effect of bioplus supplementation on performance of Madura cattle in Central Kalimantan - Ngadiyono, Nono; Hartadi, Hari; Winugroho, M; Siswansyah, Deddy Djauhari; Ahmad, Salfina Nurdin (Indonesian Animal Sciences Society, 2001)
The experiment was conducted to investigate the production performances, i.e. the growth rate, feed consumption, feed conversion and carcass percentage of Madura cattle supplemented with bioplus and palm coconut cake. Twelve (12) male Madura cattle of approximately 1.5 to 2.0 years old with an initial liveweight of 136.62+21.61 kg were used in this study, and were randomly divided into four ration treatments, namely (I) Ration composed of roughage and legume (control); (II) Roughage and legume were supplemented with bioplus; (III) Roughage and legume were supplemented with palm coconut cake; and (IV) Roughage and legume were supplemented with palm coconut cake and bioplus. Each group (unit) consisted of three cattle. The cattle were kept in feedlot system lasted in three months. The roughage and legume consisted of field grass 80%, elephant grass (Pennisetum purpureum) 10% and ground peanut straw 10%. Bioplus taken from Balitnak (Research Institute for Animal Production) Ciawi, Bogor was given at 0.5 kg/cattle and palm coconut cake was given at 2 kg/cattle, respectively. The variable measurements were average of daily gain (ADG), feed consumption, feed conversion, feed cost per gain, carcass percentage, and nutrient digestibility. The data were analyzed using a variance analyses (completely randomized design), followed by Duncanâs new multiple range test (DMRT) for the significant means. The result indicated that palm coconut cake and bioplus supplementation produce higher ADG. The ADG were 0.32; 0.38; 0.55; and 0.61 kg for treatment I, II, III, and IV, respectively. Supplementation with bioplus and palm coconut cake increased dry matter intake (DMI), organic matter (OM) and crude protein intake (CPI). Supplementation can also reduce feed conversion and feed cost per gain compared to without supplementation. Bioplus supplementation increases DM, OM, and CP digestibility. There were no significant effect of treatments on the dressing percentage, while the percentage of offal mainly skin, lung, kidney, and viscera fat were significantly different. Bioplus supplementation increased feed consumption, digestibility, and reduced feed cost per gain. Â Key words: Madura cattle, bioplus, production performance